PKM Pendampingan Pembuatan BIBIGOR (Biskuit Bihun Goreng) - Ratnah S; Nur Arisah; Mustari Mustari; Nahriana Nahriana; Sitti Hajerah Hasyim (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the activities that can add to the entrepreneurial spirit for the community is the home industry business or so-called home business in the manufacture of BIBIGOR (Biskuit Bihun Goreng). Bibigor is a new form of innovation in the field of food industry. The basic ingredient of Bibigor is biscuit. Biscuits are usually consumed unprocessed, but can now be innovated into a biscuit that is more interesting and with a new flavor. This innovation is done because in the community there are many different types of biscuits, but with the same variants and flavors and with less attractive shapes. Bibigor is a food based on Pyramid biscuits wrapped in sugar and vermicelli that has been fried. The methods used in this activity include lectures, question and answer or discussion, and training. The results obtained are (1) training on making BIBIGOR (Biskuit Bihun Goreng) responded well by the participants; (2) the high interest and motivation of the trainees greatly support the transfer of knowledge and skills from the service to the trainees, so that the training materials provided can be absorbed by all; and (3) the training products for making BIBIGOR (Biskuit Bihun Goreng) can be consumed daily and can be used as entrepreneurial products